Предмет: Алгебра,
автор: terebonka228822
Решите уравнение (2x-3)(3x+2)=(x-1)(x+1)+(5x+2)(x-14)
Ответы
Автор ответа:
0
6x^2+4x-9x-6=x^2-1+5x^2-70x+2x-28
-5x-6=-29-68x
x=-63/23
-5x-6=-29-68x
x=-63/23
Автор ответа:
0
6x^2+4x-9x-6=x^2+x-x-1+5x^2-70+2x-28
6x^2+5x-6=6x^2+2x-99
5x-2x=-99+6
3x=-93
x=-31
6x^2+5x-6=6x^2+2x-99
5x-2x=-99+6
3x=-93
x=-31
Похожие вопросы
Предмет: Геометрия,
автор: nastakravchyk12
Предмет: Английский язык,
автор: Rabika2018
Предмет: Литература,
автор: 4eburashka228777
Предмет: Алгебра,
автор: Anna010